What men owe to women : men's voices from world religions - Raines, John C.; Maguire, Daniel C. (State University of New York Press, 2001)
"What Men Owe to Women brings together a distinguished group of male scholars to address gender justice in world religions. It includes contributions representing a wide range of traditions: Islam, Judaism, Hinduism, Roman Catholicism, Protestantism, Taoism, Buddhism, and African and Native American religions. This book acknowledges the patriarchal overload of these traditions and institutes a creative search for the helpful, but neglected, resources of the traditions themselves. The contributors show how these resources support the economic and political empowerment of women and assist a rethinking of gender relations in terms of genuine mutuality. In addition they share information on their own lives and those of the women in their families that illuminate the discussion." "The book builds upon the enormous international feminist literature that has indicted the religions of the world for their insensitivity to women and their sacralization of sexism. It then looks into the causes of the fear that underlies much sexism and studies the distortion of religious symbols that supports sexism and masks men's obligations."--Jacket